Pelatihan Sistem Informasi Pengelolaan Lampu Penerangan Jalan Berbasis WEB Pada Dinas Perhubungan Kabupaten Kudus - Virgie Noval; Muhammad Arifin (Universitas KH. Mukhtar Syafaat (UIMSYA), 2026)
The management of Public Street Lighting (LPJU) at the Department of Transportation of Kudus Regency still faces challenges in data collection, monitoring, and reporting that are not yet systematically integrated. This community service activity aims to improve employees’ understanding through training on the use of a web-based LPJU management information system. The method used was a quantitative approach with a pre-experimental one group pretest–posttest design. The results showed an increase in participants’ understanding, indicated by the average pretest score of 61.8 which increased to 83.4 in the posttest. In addition, the Likert scale questionnaire results indicated that the system had good acceptance in terms of ease of use, data management efficiency, and system usefulness. Therefore, the web-based LPJU information system is considered effective in supporting more efficient and structured street lighting data management.